Gods and mortals in early Greek and Near Eastern mythology (New York)
xii, 341 sayfa
Keywords: “This volume centres on one of the most important questions in the study of antiquity – the interaction between Greece and the Ancient Near East, from the Mycenaean to the Hellenistic periods. Focusing on the stories that the peoples of the eastern Mediterranean told about the gods and their relationships with humankind, the individual treatments draw together specialists from both fields, creating for the first time a truly interdisciplinary synthesis. Old cases are re-examined, new examples discussed, and the whole range of scholarly opinions, past and present, are analysed, critiqued, and contextualised. While direct textual comparisons still have something to show us, the methodologies advanced here turn their attention to deeper structures and wider dynamics of interaction and influence that respect the cultural autonomy and integrity of all the ancient participants“ --